Impact of Fusarium Infection on Potato Quality, Starch Digestibility, In Vitro Glycemic Response, and Resistant Starch Content - Rahul Kumar Tiwari; Milan Kumar Lal; Ravinder Kumar; Sanjeev Sharma; Vinay Sagar; Awadhesh Kumar; Brajesh Singh; Rashmi Aggarwal (Journal of Fungi, 2023)
Potato dry rot disease caused by multiple Fusarium species is a major global concern in potato production. In this investigation, the tubers of cultivars Kufri Jyoti and Kufri Frysona were artificially inoculated with an individual or combined inoculum of Fusarium sambucinum and Fusarium solani. Fusarium sambucinum caused a significantly higher lesion development (p < 0.01) than Fusarium solani, irrespective of cultivars. The combined inoculum of both the Fusarium species caused significantly higher rot development (p < 0.005) in inoculated tubers. Analyses of starch and amylose content revealed that individual or mixed infection of fungi caused a significant reduction (p < 0.005) in these parameters compared to healthy tubers. The increased starch digestibility due to fungal infection caused a higher glycemic index and glycemic load. The resistant starch also deteriorated in the infected potato tubers as compared to the control. Kufri Jyoti showed a higher starch and amylose content reduction in response to the treatments compared to Kufri Frysona. The correlation analysis demonstrated a negative correlation in lesion diameter and rot volume with starch and amylose content (p < −0.80). However, the glycemic index and resistant starch were positively correlated with lesion development. Altogether, these findings highlight the progressive deterioration of quality parameters, which will be a critical concern for processing industry stakeholders and consumers.